Association Between Premorbid Beta-Blocker Exposure and Sepsis Outcomes—The Beta-Blockers in European and Australian/American Septic Patients (BEAST) Study. Issue 9 (29th April 2021) - Tan, Kaiquan; Harazim, Martin; Simpson, Andrew; Tan, Yi Chern; Gunawan, Gunawan; Robledo, Kristy P.; Whitehead, Christina; Tang, Benjamin; Mclean, Anthony; Nalos, Marek
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To examine the effect of premorbid β-blocker exposure on mortality and organ dysfunction in sepsis. DESIGN: Retrospective observational study. SETTING: ICUs in Australia, the Czech Republic, and the United States. PATIENTS: Total of 4, 086 critical care patients above 18 years old with sepsis between January 2014 and December 2018. INTERVENTION: Premorbid beta-blocker exposure. MEASUREMENTS AND MAIN RESULTS: One thousand five hundred fifty-six patients (38%) with premorbid β-blocker exposure were identified. Overall ICU mortality rate was 15.1%. In adjusted models, premorbid β-blocker exposure was associated with decreased ICU (adjusted odds ratio, 0.80; 95% CI, 0.66–0.97; p = 0.025) and hospital (adjusted odds ratio, 0.83; 95% CI, 0.71–0.99; p = 0.033) mortality. The risk reduction in ICU mortality of 16% was significant (hazard ratio, 0.84, 95% CI, 0.71–0.99; p = 0.037). In particular, exposure to noncardioselective β-blocker before septic episode was associated with decreased mortality. Sequential Organ Failure Assessment score analysis showed that premorbid β-blocker exposure had potential benefits in reducing respiratory and neurologic dysfunction. CONCLUSIONS: This study suggests that β-blocker exposure prior to sepsis, especially to noncardioselective β blockers, may be associated with better outcome. The findings suggest prospective evaluation of β-blocker use in the management of sepsis.